Comparison of Sonographic and Pathological Findings of Patients with Appendicitis in Shahid Sadoughi Hospital in the Center of Iran - Mahdi Neshan, Saeed Kargar, Mohammad Zare. Sara Sohrab Pour (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Acute appendicitis is one of the most prevalent differential diagnosis for acute abdomen. Ultrasound is a noninvasive diagnostic procedure that does not expose the patient to ionizing radiation.We intended to compare ultrasound findings as a diagnostic tool with pathology findings in patients with appendicitis who had undergone appendectomy in this study. Methods and Materials: A total of 150 patients with abdominal pain were studied in this research. Following confirmation of the diagnosis, these patients underwent surgery. SPSS Version 26 software was used to record and evaluate all demographic information, kind of underlying disease (if any), and duration of symptoms, clinical findings, pre-operation sonography findings and type of treatment and surgery. Results: The study included 150 patients, with 53.3 percent of them being female and the rest being male. Pathologically positive patients made up 78 percent of the cases analyzed. The highest sonographic finding was 6mm Appendix in terms of sonographic data (37.3 percent). The retrocecal type of the appendix was the most frequent anatomical form, accounting for 63.3 percent of all appendixes. Pathology results and sonography observations of peri-appendiceal fluid collection and peri-appendiceal fat inflammation differ significantly. The pathology findings and the ultrasonography observation of 6mm > Appendix were not significantly different. Conclusion: Inflammation of the appendix wall without necrosis and an increase in the size of the appendix (>6 mm) are the key ultrasound findings in support of a diagnosis of uncomplicated appendicitis.